The Development of Islamic Teaching Methodology by Using Project Based Learning Model - Karolina, Asri; Wari, Karliana Indra; Anbia, Rejabil; Adelia, Putri (Institut Agama Islam Negeri (IAIN) Curup, 2023)
This research aims to develop a project-based learning model and PAI Teaching Methodology (MPP) teaching materials based on valid media integration to improve students' collaboration, communication, critical thinking, and creative thinking (4C'S) abilities. The type of research used in this research is Research and Development. The procedures for this research are: 1) analysis of perceptions and identification of the needs of lecturers and students of the Islamic Religious Education (PAI) Study Program, Faculty of Tarbiyah IAIN Curup regarding the syntax and teaching materials of the PAI Teaching Methodology used, 2) design planning for the development of a project-based learning model and teaching materials, 3) development of the initial design for the development of the project-based learning model and teaching materials, 4) testing the validity of the prototype of the project-based learning model and teaching materials (self-evaluation and expert review. The results show that: 1) 72.61% of lecturers and 28.41% of students stated that the PAI Teaching Methodology teaching materials used so far were inappropriate and inappropriate. 98.87% of lecturers and 45.01% of students stated that needed. 2) design planning for the development of teaching materials using a project-based learning model based on the integration of Canva and QR code media and containing 15 chapters of 4C'S based on needs analysis. 3) 44.4% of experts stated that the RPS was by the RPS component loads, and 55.6% of experts stated that the RPS was very suitable for the RPS component loads. Development of 15 Chapter MPP teaching materials with 115 pages. 4) The self-evaluation shows that the PAI Teaching Methodology teaching materials based on are worthy of validation. PAI Teaching Methodology teaching materials based on the integration of Canva and QR code media were declared valid by the expert team by obtaining an average score of 88.475 in the appropriate category.